O‘ZBEKISTON RESPUBLIKASI MA’MURIY-HUDUDIY TUZILISHINING TARIXIY-GEOGRAFIK TAHLILI - Qurbonov, Sh.B.; Pirnazarov, J.B. (SCIENCE and SOCIETY, 2024)
The article reveals the historical and geographical aspects of the administrative-territorial division of the Republic of Uzbekistan. Characteristics are given of the formation of administrative units of the country, changes in their number and factors that influenced these changes.